The role of NT-proBNP in the diagnosis of diastolic heart failure and its correlation with echocardiography (British Journal of Multidisciplinary and Advanced Studies, 2023)
The primary aim of the current investigation was to evaluate the role of NT-proBNP in the diagnosis of diastolic heart failure and its correlation with echocardiography. Hospital based observational and analytical study undertaken on a total of 65 patients of diastolic heart failure fulfilling clinical inclusion criteria. The enrolled patients had a mean age of 54.5 years with a female preponderance (33 females vs. 32 males). Patients underwent clinical evaluation and echocardiography examination. NT-proBNP estimation was done using autoanalyzer working on principle of electrochemiluminisense. Patients were divided into various grades of diastolic dysfunction on the basis of echocardiography. Statistical analysis was done to find the significance of levels of NT-proBNP and its correlation with the grading of diastolic heart failure. There was a statistically significant higher level of serum NT-proBNP in patients with diastolic heart failure and the increasing levels were directly proportional to severity of diastolic dysfunction. The mean level of NTproBNP increased from 361.08 pg/ml to 3570 pg/ml in increasing severity of diastolic dysfunction. Results suggested positive correlation of rising NT-proBNP levels with increasing severity of diastolic dysfunction.